Attitude of Mothers Regarding Use of Low Osmolar Oral Rehydration Solution (ORS) in Diarrhea. An Experience in Rural Area of Sindh (Medical Forum Monthly, 2024)
Objective: To assess the knowledge and attitude of mothers regarding use of low osmolar Oral Rehydration Solution (ORS) in diarrhea and to find out the causes of under use of ORS and knowledge regarding ORS. Study Design: cross sectional study. Place and duration: Pediatric OPD civil hospital Badin with collaboration of Department of Pharmacology and therapeutics Mohammad Medical College Mirpurkhas patient and method.100 children of age 6 months to five years with various degrees of dehydration were enrolled in study. A questionnaire was given to mothers Patients and Methods: It was a prospective, cross sectional and descriptive study conducted at Peadiatric OPD civil hospital Badin with collaboration of Department of Pharmacology and therapeutics Mohammad Medical College Mirpurkhas.100 children of age 6 months to five years with various degrees of dehydration were enrolled in study. A questionnaire was given to mothers. A proforma was designed for question and answers. Data was analyzed. Results: 100 children were enrolled, out of which 55(55%, 28.0 ± 16.02) were under 2 years of age, 45(45%, 23.0 ± 13.13) were under 5 years of age, 62(62%, 31.50 ± 18.0) were males, 38(38%, 19.50 ± 11.11) were females. 70(70%, 35.01 ± 18.53) children were brought to OPD by mothers. 30(30%, 15.50 ± 8.80) were brought by parents. 60(60%, 30.50 ± 17.46) attendants were uneducated and 40(58%, 20.50 ± 11.69) educated. 58(58%, 29.50 ± 16.89) children had duration of illness 1-3 days. 42(42%, 21.50 ± 12.27) children has >3 days. 35(35%, 18.0 ± 10.25) children were with loose motion and vomiting. 29(29%, 15.0 ± 8.51) were with loose motion and fever. 30(30%, 15.50 ± 8.80) had only loose motion and 6(6%, 3.50 ± 1.87) with blood in stool. Out of 100 only 22(22%, 11.50 ± 6.49) children were given ORS and 78(78%, 39.50 ± 22.66) were not given ORS. Only 16(16%8.50 ± 4.76), mothers knew the proper way to prepare the ORS. The P-value of all variables were not significant in table no one, but P-value significant in table two statistically. Conclusion: This study showed that there is insufficient use of ORS in rural areas of Sindh and those who use it do not know the proper way to prepare and serve it, As majority of mothers were uneducated and did not have knowledge regarding ORS use in diarrhea false belief and non availability were other reasons for under use of ORS. This needs to work harder in rural areas of Sindh, to educate mothers regarding use of ORS and recognition of signs of dehydration and initial home care. This task can easily be performed this needs cooperation of NGO and active participation of by lady health workers if they are fully committed and supported.